As cooperativas de crédito e a implementação da política de inclusão financeira no Brasil - Greatti, Ligia (2017)
This study, in general terms, analyzes issues connected to relations between State and society in public policy implementation processes in Brazil, focusing on process that resulted in policy of financial inclusion. The objective that guides development of research refers to the role played by actors located in non-state sphere, particularly Credit Cooperatives, in processes of public policies implementation and, mainly, how these actors relate to actors positioned in state sphere, particularaly in public policy coordination. Looking for providing theoretical support for the research, a literature survey was carried out on public policies, implementation process and its actors, the policy of financial inclusion and on credit cooperativism. Then, the approach proposed by Subirats et al. (2012) in order to analyze relationship between credit cooperatives, as actors who implement financial inclusion policy and governmental actors coordinating this policy, in particular Brazilian Central Bank. Through this approach, the policy content was analyzed, actors with their values, ideas and interests, the resources they mobilize and institutional rules that surround them, and how these elements influence relations established between the actors. Therefore, it was used documentary research and semi-structured interview for data collection, which contents were analyzed with the help of Atlas TI Software. It was observed that the process of implementing financial inclusion policy is influenced by these elements, which motivate and condition relationships. Conclusions of the study point that cooperatives involved in process effectively succeed in influencing public policy implementation and that relations between them and Brazilian Central Bank occur in cooperation way, which is only due to the fact that exists consensus among them about public problem faced, of common values and interests in face of financial inclusion policy, mobilizing resources autonomously and, in certain situations, through negotiation, also with dialogues and discussions on institutional norms that involve them. Relationships between these actors in process of implementing financial inclusion policy went through a long period of reflections and debates, which have continued constantly until present day, thus strengthening existing cooperation between them.